A satisfaction function and distance measure based multi-criteria robot selection procedure - KENTLİ, AYKUT (TAYLOR & FRANCIS LTD, 2011)
A multi-criteria decision-making model for a robot selection problem is presented in this article. The proposed model uses satisfaction function to convert various robot attributes into a unified scale. Further, a distance measure technique is used to ascertain the highest ranked candidate-robot. The proposed model is tested on the data from the open literature. An example case is presented and the results so obtained considering different attributes are compared with the results obtained earlier utilising the same data.
Keywords: robot selection; satisfaction function; distance measure; multi-criteria decision-making; DECISION-MAKING APPROACH; GOAL-PROGRAMMING-MODEL; INDUSTRIAL ROBOTS; TECHNOLOGY SELECTION; SYSTEM; PERFORMANCE; METHODOLOGY; REGRESSION; DESIGN; TOPSIS